Russian literature in the mirror of the Perm periodicals (Филологический класс, 2008)
We consider a bibliographic reference book in this review "Literary Life of Russia in the late XIX - early XX century in the periodical press (1890-1917)". Handbook is a compilation of literary criticism and bibliographies published in the newspapers over thirty years of the Permian. The review draws attention to the genre range of the publications and the structure of the directory. A high rating is due to labor Perm scientists look at a particular solution of the relationship between the national laws of literary-historical process and their regional and local implementation.